Peran Kepala Desa Dalam Ketertiban Pasar Desa Sukajadi Kecamatan Sadananya Kabupaten Ciamis - Noer Syamsi (Gunung Djati Conference Series, 2023)
The village market is an important asset that is expected to meet the needs of rural communities and contribute to the village economy. However, the lack of economic knowledge from market managers and weak management by the village government or local traders' organizations has resulted in the market not developing optimally. In this study, a descriptive method was used with interview and observation techniques to collect data according to the problems studied. The data used is qualitative data, which is analyzed through observation and discussion of the role of the village head in managing the village market. The research results show that the village is the smallest unit in the state administration system that has its own government structure. Village markets play an important role in meeting the daily needs of village communities and can become centers of economic and social activity. Good village market management includes transparent management, security, waste handling, order, maintenance, and customer care.